The pay transparency dilemma: Development and validation of the Pay Information Exchange Preferences Scale. - Smit, Brandon W.; Montag-Smit, Tamara (Journal of Applied Psychology, 2019)
Although calls for pay transparency in the workplace are growing, it remains unclear which factors determine when and why employees exchange pay information. We use a social comparison theory lens to identify the pay transparency dilemma, wherein pay information exchange can create benefits by reducing uncertainty and verifying equitable pay, but simultaneously risks straining interpersonal relationships and damaging reputations. To examine individual differences in employee sensitivity to the risks and benefits presented in this dilemma, our research develops a measure of pay information exchange preferences with two facets: information sharing preferences and information seeking preferences. Across eight samples, we present evidence that supports the content, construct, and criterion validity of these measures. Overall, these findings support the idea that social comparison processes play a key role in shaping employee pay information exchange preferences and behaviors. This new instrument has the potential to catalyze future theoretical development and research to aid practitioners in making evidence-based decisions about pay communication policies. (PsycINFO Database Record (c) 2019 APA, all rights reserved).